Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jcm10132985
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predicting Factors for Subcutaneous Emphysema Associated with Robotic-Assisted Laparoscopic Radical Prostatectomy: A Retrospective Single-Center Study

Abstract: Objectives: Subcutaneous emphysema (SCE) is a complication associated with laparoscopic surgery. Severe SCE complicated by excessive hypercarbia may afford detrimental effects in surgical patients with cardiac dysfunction. Robotic-assisted laparoscopic radical prostatectomy (RALP) has several predisposing factors that contribute to SCE. The main purpose of our single-center retrospective study was to determine the preoperative and intraoperative predicting factors for SCE associated with RALP and to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In the Trendelenburg position, body fluid moves from the legs toward the heart by gravitational displacement due to body inversion [ 13 ]. In addition, the RARP procedure can cause subcutaneous emphysema around the neck [ 14 ]. Moreover, the cephalad move of the patient occurs due to the Trendelenburg position in RAPS [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Trendelenburg position, body fluid moves from the legs toward the heart by gravitational displacement due to body inversion [ 13 ]. In addition, the RARP procedure can cause subcutaneous emphysema around the neck [ 14 ]. Moreover, the cephalad move of the patient occurs due to the Trendelenburg position in RAPS [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic-assisted laparoscopic radical prostatectomy procedure, because of the presence of multiple surgical ports, prolonged surgery duration and its peculiar position, can favor the development of subcutaneous emphysema. Yamamoto et al [6 ▪ ] found the presence of subcutaneous emphysema in 24% of the patients who underwent chest X-rays. Nevertheless, none of these patients showed any postoperative pulmonary complications, such as loss of upper airway patency or respiratory failure.…”
Section: Ventilatory Managementmentioning
confidence: 99%
“…Extrapolating the experience from laparoscopic surgery, risk factors for SCE include multiple abdominal entries, long operative times of ≥200 minutes, five or more laparoscopic ports, and age older than 65 years [17,18]. A retrospective of robotic prostatectomy showed that BMI <25 kg/m 2 and partial pressure of endtidal CO 2 of ≥ 46 mmHg were two independent factors for SCE [19]. SCE can lead to laryngeal edema, tracheal compression, and subsequently hypercarbia and respiratory acidosis [17].…”
Section: Inherent Risks Of Operationsmentioning
confidence: 99%
“…SCE can lead to laryngeal edema, tracheal compression, and subsequently hypercarbia and respiratory acidosis [17]. The treatment of hypercarbia by increasing pulmonary ventilation, however, is limited by Trendelenburg position and pneumoperitoneum [19].…”
Section: Inherent Risks Of Operationsmentioning
confidence: 99%